AB0134 Are salivary mucins able to trigger a pro-inflammatory response?. (23rd January 2014) - Barrera, M.-J.; Aguilera, S.; Hermoso, M.; Langjahr, P.; Cortés, J.; Castro, I.; Molina, C.; Gonzalez, S.; Alliende, C.; Bahamondes, V.; Sepúlveda, D.; Leyton, C.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disease that affects lacrimal and salivary glands, whereby SS-patients complain of eye and mouth dryness. Salivary-acinar-cells of SS-patients display alterations in cell polarity affecting the localization and function of proteins involved in regulated exocytosis. In salivary-glands (SG) from SS-patients, the levels of mRNA and protein for VAMP8, STX4 and STX3 were altered. STX4, STX3, SNAP-23 and VAMP8 relocated from the apical to the basal region of acinar-cells. Increased formation of SNARE-complexes in a manner independent of external stimuli for secretion was detected. Strikingly, mucins were detected in the extracellular matrix (ECM). Ectopic mucins and the alterations in SNARE protein localization are indicative of atypical exocytosis. Aberrantly localized mucins could favor a pro-inflammatory response, which may represent an important initial step in the pathogenesis of this disease. Objectives: To determine if exogenous mucins are able to induce pro-inflammatory cytokines expression in cultured human submandibulary gland cells (HSG) and also to define the receptors involved. Methods: HSG-cells were cultured in complete DMEM F12 + 5% FBS medium and stimulated with mucins at different concentrations and times. The expression of pro-inflammatory cytokines and their receptors were determined by qPCR. As controls, LPS stimulation and TLR2 plus TLR4 basal expression were measured. TLR4 participation was evaluated using inhibiting specific peptides and blocking antibodies. Results: All cytokines studied showed a significant increase of mRNA levels after 24 hours of mucin stimulation. The expression of IFN-γ and IL-10 was also assayed; however, HSG cells did not express these cytokines in basal conditions or under mucin stimulation. Through its large domains of sugar residues, mucins could be recognized by pathogen-related receptors such as Toll-like receptors (TLR), specifically TLR4. We evaluated the TLR4 receptor mRNA basal levels, as well as mRNA receptors for some of the cytokines studied. HSG cells express TLR4 and cytokine receptors for TNF-α, IFN-α, IFN-β, IFN-y, IL-6 and IL-1β. HSG cells treated with LPS showed a significant increase of TNF-α and IL-6 expression. Levels of cytokines expression relative to h18S in HSG cells stimulated with mucins are similar to those found with a high concentration of LPS. Then, we assessed if HSG cells would recognize mucins through TLR4 using an inhibitor peptide of TIRAP (an adapter molecule downstream signaling pathway of TLR2 and TLR4). TBX peptide blocked the induction of IL-6 and TNF-α expression in HSG cells stimulated with mucins and LPS. Conclusions: Salivary mucins induce pro-inflammatory cytokines. This result suggests that the cytokine-inducing action by mucins is mediated by a TLR4-dependent pathway, because the induction of both cytokines by LPS also was reversed in the presence of TBX. This response could be active in the ECM of SG from SS-patients and eventually promote the infiltration of inflammatory cells, which may represent an important initial step in the pathogenesis of this disease. Acknowledgements: Work was supported by grants Fondecyt-Chile 1120062, CONICYT-Chile PhD fellowship (MJB and JC) and BEP-fellowship (DS). Disclosure of Interest: None Declared